Densidad de población de pequeños mamíferos en dos comunidades del bosque andino (1988)
The density of small mammals living in two communities of the Andean Forest of the eastern slopes of the Sabana de Bogota in the western Cordillera (Cerro Cueva Grande and Cerro Majuy), was studied. The two places were tramped for six months between March and September 1981, using livetraps and snaptraps during six days per month in each community. Densities for each species were obtained by the Hayne Melbod, the Lincoin and Jolly Indexes and by absolute density. Flora, climate and soil characteristics and their influence in the species were also considered in the two communities.